2017
DOI: 10.1210/jc.2016-4025
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib-Induced Changes in Thyroid Hormone Levels in Patients Treated for Hepatocellular Carcinoma

Abstract: These in vivo data suggest that sorafenib affects TFTs on multiple levels. Our in vitro experiments suggest a possible role of sorafenib-induced inhibition of T3 transport into the cell by MCT8 and MCT10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Supportive drugs to control AEs such as hypertension will expand the use of lenvatinib. With respect to fatigue, several reports recommend the use of thyroid hormone preparations or steroids [24,29]. In addition, in our study, 20 patients required administration of thyroid hormone preparations to combat fatigue caused by lenvatinib treatment.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Supportive drugs to control AEs such as hypertension will expand the use of lenvatinib. With respect to fatigue, several reports recommend the use of thyroid hormone preparations or steroids [24,29]. In addition, in our study, 20 patients required administration of thyroid hormone preparations to combat fatigue caused by lenvatinib treatment.…”
Section: Discussionmentioning
confidence: 79%
“…The incidence rate of any grade and grade ≥ 3 fatigue was 53.1% and 16.0%, respectively (Figure 2A). Based on previous reports that hypothyroidism and hypoadrenocorticism are correlated with fatigue related to anti-angiogenic drugs (AAD) [17,[22][23][24], we assessed the patients' levels of free T4, thyroid-stimulating hormone (TSH), cortisol, and acetylthiocholine iodide (ACTH). Among the 135 patients, thyroid function was evaluated before and after treatment in 118 patients.…”
Section: Mechanisms For the Occurrence Of Fatigue In Lenvatinib Treatmentioning
confidence: 99%
“…One of the reasons may be that the onset of hypothyroidism is delayed and long-term and may even persist when VEGFR-TKIs treatment is paused. 22 However, signals for hyperthyroidism were detected with the use of all the VEGFR-TKIs, except for vandetanib. This revealed that the use of VEGFR-TKIs may be associated with hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…The tricyclic antidepressant desipramine inhibits both MCT8 and MCT10 (194), whereas the flavonolignan silychristin appears to be a specific inhibitor of MCT8 (79). Moreover, several tyrosine kinase inhibitors have been found to interfere with MCT8 and MCT10 function through noncompetitive Review inhibition (195)(196)(197)(198). Although not as extensively studied as short MCT8, the long isoform of human MCT8 also efficiently transports iodothyronines (80,199).…”
Section: Substrate Specificity and Transport Directionmentioning
confidence: 99%